Tax App: Aplikasi Perpajakan Berbasis App Mobile di CV. Shanjaya Group Webbing - Alfianto, Dani; Haddraturafilah, Arya; Susanto, Fredy; Maisaroh, Siti (Universitas Batanghari Jambi, 2025)
The quality of the software can be seen from the functionality of the application system, whether it meets the user's needs or whether it may be detrimental to the system owner and user. For software testing, there are several methods used by testers to evaluate software, namely Black Box Testing and White Box Testing. In this research, the testing method used is Black Box by applying the Equivalence Partitioning technique to evaluate the TaxApp android-based application on CV. Shanjaya Group Webbing. The research stages are determining system function, designing test cases, conducting testing, and drawing final conclusions. Based on the results of black box testing, it was found that the application runs according to its function, namely that users can access the application, manage payment data and categories and the application can print reports per period. The results of the research obtained an application that is able to carry out the recording process more easily and reduce the error rate in recording data, and the data is automatically saved and can be viewed at any time and anywhere.